2018
DOI: 10.3892/ijmm.2018.3504
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin ameliorates diabetic nephropathy by blocking TGF-β1/Smad signaling pathway

Abstract: Diabetic nephropathy (DN) is the leading cause of end-stage failure of the kidney, but the efficacy of current strategies available for the prevention of DN remains unsatisfactory. The purpose of this study was to assess whether sitagliptin (SIT) has therapeutic potential for prevention of DN and to investigate its possible mechanism. The effects of SIT on DN were investigated in rats with type 2 diabetes mellitus (T2DM) and rat mesangial cells (MCs) induced by high glucose. T2DM rats were administered at a do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 36 publications
2
34
2
1
Order By: Relevance
“…As to the anti-fibrotic action of sitagliptin, we have no mechanism to offer yet. Although DPP4 inhibition has previously been demonstrated to directly inhibit canonical TGFβ signaling via Smad2 in renal fibrosis 60 and TGFβ-mediated myoFB-differentiation by interfering with ERKsignaling 61 , we were not able to confirm these mechanisms in skin FBs. Possible explanations for alternative the anti-fibrotic action of sitagliptin could be interactions with CXCL12/SDF1 (Stromal derived factor 1), a substrate of DPP4 62 which was found to promote scar formation 63 , or with components of the ECM, such as fibronectin , which have been shown to bind latent TGFβ 19 , or DPP4 induced cleavage of growth factors or receptors 62 .…”
Section: Discussioncontrasting
confidence: 72%
“…As to the anti-fibrotic action of sitagliptin, we have no mechanism to offer yet. Although DPP4 inhibition has previously been demonstrated to directly inhibit canonical TGFβ signaling via Smad2 in renal fibrosis 60 and TGFβ-mediated myoFB-differentiation by interfering with ERKsignaling 61 , we were not able to confirm these mechanisms in skin FBs. Possible explanations for alternative the anti-fibrotic action of sitagliptin could be interactions with CXCL12/SDF1 (Stromal derived factor 1), a substrate of DPP4 62 which was found to promote scar formation 63 , or with components of the ECM, such as fibronectin , which have been shown to bind latent TGFβ 19 , or DPP4 induced cleavage of growth factors or receptors 62 .…”
Section: Discussioncontrasting
confidence: 72%
“…The TGF-β1/Smads signaling pathway plays an important role in DN pathogenesis, which includes podocyte injury, basement membrane thickening, mesangial cell proliferation, renal cell apoptosis, and epithelial cell interstitial transformation, among others [32,33]. Studies have confirmed that abnormal activation of the TGF-β1/Smad signaling pathway may be the main cause of renal fibrosis in diabetic nephropathy patients [34].…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies suggested that the Smad family could act as signal integrators among inflammatory or fibrogenic pathways mediating tissue inflammation [29,30]. On the other hand, a pleiotropic cytokine TGF-b was considered as the main mediator in the development of different pathological disorders including fibrosis, angiogenesis, immunosuppression, post-trauma repair, and inflammation and its effect was mediated by the Smad 2 and Smad 3 signaling molecules [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a pleiotropic cytokine TGF-b was considered as the main mediator in the development of different pathological disorders including fibrosis, angiogenesis, immunosuppression, post-trauma repair, and inflammation and its effect was mediated by the Smad 2 and Smad 3 signaling molecules [31][32][33]. These molecules were activated in different animal models of renal diseases as obstructive kidney diseases, nephrectomy and diabetic nephropathy [29,30,34].…”
Section: Discussionmentioning
confidence: 99%